University student’s internalising problems in the context of mental support in Poland – a Latent Profile Analysis - Joanna Frankowiak; Martyna Kotyśko (Studia z Teorii Wychowania)
University students are exposed to a number of stressors that may affect their mental state. However, they do not receive sufficient psychological support, although the demand for it seems to be increasing. The current study examines what psychological profiles can be identified among students based on how often different subjective problems affect their functioning. The participants were 1,499 Polish students (63% women, ages 18-26, 7.4% had previously used professional support). Five profiles, differing in the intensity of the seven internalising problems, were identified in latent profile analysis: in crisis (IC, 2.1%); increased risk − with (IR-S, 7.5%) and without suicidal thoughts or behaviours (IR-NS, 8.8%); increased risk − experiencing tension (IR-T, 19.1%); and not needing support (NNS, 62.5%). Gender, place of origin, and the use of professional psychological support significantly differentiated the profiles. The results of the study allow us to draw indications that are important for the design of preventive measures in the academic environment. Particularly important is the implementation of activities that fall into the area of selective prevention, targeting IR-NS and IR-T groups (about 28% of survey participants).This is supported by the percentage of people belonging to these groups, as well as the nature of the difficulties they are facing.